Microseismic Monitoring of Energy Changes in Deep Tunnels during the TBM Tunneling of the Jinping II Hydropower Station - Duanyang Zhuang; Ke Ma; Chunan Tang; Zhengzhao Liang; Zhenwei Wang (Advances in Civil Engineering)
The TBM tunneling at the Jinping II hydropower station in Southwest China has received extensive concerns around the world because of its large engineering scale and the high rockburst risks faced in the tunnel advancement. The associated energy changes of rockbursts and control method for safe TBM tunneling are to be further investigated. A movable microseismic (MS) monitoring system was established to capture the MS events and rockbursts when the TBM excavated the headrace tunnel #1 at the Jinping II hydropower station. The spatial and temporal patterns of the energy changes in the tunnel rock masses were studied. Meanwhile, the evolution of a rockburst encountered in front of the TBM excavation face was revealed, and the performance of the top pilot tunnel method on the reduction of the rockburst risks in the headrace tunnel #1 was evaluated based on the energy changes of the surrounding rock masses. It can be concluded that energy accumulation and energy release firstly occurred in the surrounding rock masses at the southern end of the top pilot tunnel section of the headrace tunnel #1. Then, energy transference of the rock masses took place from the southern end to northwest of the top pilot tunnel giving rise to the occurrence of a moderate rockburst about 30 m in front of the tunnel. However, no rockbursts appeared when the TBM excavated through the top pilot tunnel section of the headrace tunnel #1. Therefore, the top pilot tunnel method really works in reducing the risks of rockbursts during the TBM tunneling in deep tunnels.